A Review of Trend of Leprosy Situation in Jamnagar District of Gujarat - Sanghavi , Mithun M (National Journal of Community Medicine, 2012)
Objectives: This study was conducted to identify the trend of leprosy in Jamnagar district and to evaluate the impact of national leprosy elimination Program in Jamnagar District. Methodology: This was a retrospective study conducted by analyzing records of District Tuberculosis Center, Jamnagar from April 2000 to March 2011. Different variables like Prevalence rate, Annual New case detection rate, Proportion of MB cases, Grade 2 disability cases, child cases and female cases among new cases etc. were covered in the study. Results: There was a decrease in prevalence of leprosy in Jamnagar district. Annual case detection rate was decreasing from 12.53 per lakh population in the year 2000–01 to 2.36 per lakh population in the year 2010-11. Proportion of cases released from treatment was rising during initial six years followed by decline during next two years. Child ratio had been declined during the year 2008-09 followed by rise in last two years. There is rising trend of MB cases over years. The trend of deformity and female cases among new cases was not consistent. Conclusions: The national leprosy elimination Program has impressive impact in maintaining the elimination level of leprosy in a district. Some sincere efforts like improving surveillance activities, IEC activities, improving cases released from treatment etc are still required for further improving leprosy situation in a district.